2006
DOI: 10.1038/nature05228
|View full text |Cite
|
Sign up to set email alerts
|

An early evolutionary origin for the minor spliceosome

Abstract: The minor spliceosome is a ribonucleoprotein complex that catalyses the removal of an atypical class of spliceosomal introns (U12-type) from eukaryotic messenger RNAs. It was first identified and characterized in animals, where it was found to contain several unique RNA constituents that share structural similarity with and seem to be functionally analogous to the small nuclear RNAs (snRNAs) contained in the major spliceosome. Subsequently, minor spliceosomal components and U12-type introns have been found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
145
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(156 citation statements)
references
References 28 publications
11
145
0
Order By: Relevance
“…These structures have received substantial interest in the past, as explified by the following non-exhaustive list of references covering a diverse set of animal species: Homo sapiens U1 [54], U2 [25], U4 [37], U5 [6,79], U6 [25], U11 [66,51,82], U12 [66,51,82] and U4atac [72], Rattus norvegicus U1 [37], U4 [37], U5 [37], Gallus gallus U4 [37], U5 [6], Xenopus laevis U1 [18], U2 [47], Caenorhabditis elegans U1, U2, U5, U4/U6 [84], Drosophila melanogaster U1 [54,56], U2 [56], U4 [56], U5 [56], U4atac/U6atac, U6atac/U12 [59], Bombyx mori U1 [76], U2 [75], Asselus aquaticus U1 [3], Ascaris lumbricoides U1, U2, U5, U4/U6 [70]. Large changes in snRNA structures over evolutionary time were recently reported for hemiascomycetous yeasts [50].…”
Section: Secondary Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…These structures have received substantial interest in the past, as explified by the following non-exhaustive list of references covering a diverse set of animal species: Homo sapiens U1 [54], U2 [25], U4 [37], U5 [6,79], U6 [25], U11 [66,51,82], U12 [66,51,82] and U4atac [72], Rattus norvegicus U1 [37], U4 [37], U5 [37], Gallus gallus U4 [37], U5 [6], Xenopus laevis U1 [18], U2 [47], Caenorhabditis elegans U1, U2, U5, U4/U6 [84], Drosophila melanogaster U1 [54,56], U2 [56], U4 [56], U5 [56], U4atac/U6atac, U6atac/U12 [59], Bombyx mori U1 [76], U2 [75], Asselus aquaticus U1 [3], Ascaris lumbricoides U1, U2, U5, U4/U6 [70]. Large changes in snRNA structures over evolutionary time were recently reported for hemiascomycetous yeasts [50].…”
Section: Secondary Structuresmentioning
confidence: 99%
“…Another class of "non-canonical" introns with AT-AC (and rarely GT-AG [71]) boundaries is excised by the minor spliceosome [61], which contains the snRNAs U11, U12, U4atac, U5, and U6atac. Just as the major spliceosome, the minor spliceosome is present across most eukaryotic lineages and traces back to an origin very early in the eukaryote evolution [9,44,65]. Recently it was found that the minor spliceosome can also act outside the nucleus and controls cell proliferation [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was first apparent from the sequence of the U6atac snRNA from the plant Arabidopsis thaliana, which is, overall, 65% identical to mammalian U6atac (Shukla and Padgett 1999). More recent work has identified U12-dependent introns and/or spliceosomal components in several organisms from deep branches of eukaryotic phylogeny (Russell et al 2006). Sequence analysis of a large number of genomes for spliceosomal snRNAs has identified putative U6atac snRNA homologs in many of these lineages (Lopez et al 2008).…”
Section: The U6atac Snrna 39 End Domain Is Phylogenetically Conservedmentioning
confidence: 99%
“…Thus, although four snRNPs are unique to the minor spliceosome, the same U5 snRNP is shared by the minor and major spliceosomes. The minor spliceosome has subsequently been studied with respect to its protein composition and mechanism (8,9), as well as its phylogenetic distribution and evolutionary origins (10). The minor spliceosome excises Ϸ1 in 300 introns from human pre-mRNAs (11)-which encode proteins with a wide range of functions (12)-consistent with the lower abundance (Ϸ1%) of its snRNPs relative to those of the major spliceosome.…”
mentioning
confidence: 99%